Penanaman Karakter Kewirausahaan Di TK Alam Al-Azhar Kutai Kertanegara - Wildan Saugi; Iin Sundari; Agustiah Agustiah (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2020)
This research aims to find out the implementation of entrepreneurship charac- ter building on children at early age at TK Alam Al-Azhar Loa Janan Kutai Kertanegara, the activities carried out to build the entrepreneurship characters, supporting and ob- structing factors in the process of the implementation. This research is field research with a qualitative approach. The data collection techniques used observations, interviews, and documentation. The research data was analyzed with the descriptive technique. The result shows that entrepreneurship character building is carried out through the integration of entrepreneurship characters such as discipline, independent, honest, leadership, commu- nicative, creative, hard work, risk-taking, patient, and diligent with daily activities at school. TK Alam also design and implement specific activities related to and aiming to introduce entrepreneurship. Activities at TK Alam Al-Azhar to build entrepreneurship characters are daily habituation activities, schedule of watering plants and feeding fishes, schedule of being imam of Dhuha prayer for male students, family day, peak of theme such as visit, market day, gardening, vegetable harvest, and fishing. Supporting factors are large and fertile soil, natural facilities such as garden and fish pool, cooperation be- tween school and societies, school location at Poros street Samarinda-Balikpapan, and experienced human resources. The obstructing factors are the condition of slope land which is prone to slide, the condition of the pools which are not permanent, the condition of the footpaths to the pools and the garden which are slightly far and slippery after rain- ing, and the plant maintenance which is not routine during a long holiday.